Efficacy of Amphotericine B Ddrug Against Promastigote and Axenic Amastigote of Leishmania Dononvani in Vitro - M. Abbas, Zhor; H. Zghair, Khawla; M. Al-Bashir, Nada (Iraqi Journal of Science, 2023)
Leishmania are protozoan parasites belonging to the family Trypanosomatidae that cause high morbidity and mortality levels with a wide spectrum of clinical syndrome. This study aimed to investigate the effect of liposomal amphotericine B (AmBisome) drug on promastigote and axenic amastigote stages of Leishmania donovani isolate (MHOM/IQ/2005/MRU15)in comparison with pentostam SbV drug. Different concentrations of AmBisome and SbV drugs were investigated against Leishmania donovani promastigote and axenic amastigote. The ICR50R values of SbV and AmBisome drugs on promastigote were10.12 mg/ml and 2.21μg/ml, respectively, while they were 0.77μg/ml for axenic amastigote for both drugs. The present study concluded that axenic amastigote was more sensitive than promastigote against both drugs, and AmBisome drug showed high effectiveness against both stages with low concentrations in comparison with pentostam